Prosedur Inventory pada Proses Penerimaan, Penyimpanan, dan Pengeluaran Barang Umum di Pt. Semen Padang - Ifan Cahyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The management of general goods is an important part of inventory management in manufacturing companies. PT Semen Padang, as the oldest cement industry company in Indonesia, requires a structured inventory system to support smooth operations. This study aims to describe the procedures for receiving, storing, and issuing general goods at PT Semen Padang. The writing method uses literature studies and general warehouse procedure analysis. The discussion results show that inventory management is carried out through: (1) document verification and physical inspection in the receiving process, (2) storage arrangement based on goods classification and the application of FIFO/FEFO principles, and (3) systematic recording in the goods issuance process through ERP applications. This implementation aligns with modern inventory management theory, which emphasizes meticulous record-keeping, stock accuracy, and efficient goods flow.